Assessment of physical and special training of border guards to the profession the first age group - Volkov V.L (Kharkov National Pedagogical University, 2012)
The problem of managing the physical and special training of troops of various arms in defense reform was considered in the article. Determine the status of development of physical and special abilities of military guards 21-30 years. The study involved 48 non-commissioned officers, warrant officers and officers who carry out official duties under the contract. It is developed a differentiated assessment of physical and specially trained employees of the State Border Service the first age group